2021
DOI: 10.18521/ktd.880070
|View full text |Cite
|
Sign up to set email alerts
|

Evde Bakım Hastalarında D Vitamini Düzeylerinin Değerlendirilmesi

Abstract: Objective: Vitamin D deficiency has become an epidemic for all age groups in the world. The aim of this research is to evaluate the vitamin D deficiency in-home care patients and related lifestyle reasons. Method: This research is done on Home Care patients registered to İstanbul Şişli Hamidiye Etfal Training and Research Hospital between January 2015 – February 2016. After getting the patients’ vitamin D records retrospectively, we have inquired patients if they have regular exposure to sunlight, whether they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the study of Dev et al (19) on a group of cancer patients, the rate of vitamin D deficiency was found to be 47%. Lovell et al (20) found that 88% of palliative care patients suffered from vitamin D deficiency, Vollbrach (15) found that 79.7% of palliative patients suffered from vitamin D deficiency and Yılmaz and Toprak (21) found that 70.3% of domiciliary care patients suffered from vitamin D deficiency. The findings in our study were similar to these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Dev et al (19) on a group of cancer patients, the rate of vitamin D deficiency was found to be 47%. Lovell et al (20) found that 88% of palliative care patients suffered from vitamin D deficiency, Vollbrach (15) found that 79.7% of palliative patients suffered from vitamin D deficiency and Yılmaz and Toprak (21) found that 70.3% of domiciliary care patients suffered from vitamin D deficiency. The findings in our study were similar to these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one previous study reported that in patients with severe respiratory diseases such as COPD, microbial infection can cause airway stenosis, which can lead to serious complications. [ 53 ] Therefore, the prevention effect of MHGT for LRTI might helpful for not only alleviating the burden of medical care but also reducing severity of respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%